Ekologisk retorik och urbana realiteter: Om natur, rättvisa och planeringsdiskurser i Västra Hamnen - Ekman,Vilda (2025)
This study critically examines how nature is mobilized in the urban planning discourse of Västra Hamnen, Malmö, and explores the implications for justice and the distribution of green infrastructure. Combining Urban Political Ecology (UPE) with Nesbitt et al.’s (2018) framework on Urban Green Equity, the analysis integrates thematic readings of planning documents, site observations, and an informal conversation with a resident. The study finds that nature in Västra Hamnen functions not only as an ecological resource, but as a symbolic, institutional, and technical construct used to legitimize visions of sustainability, growth, and modernity. Through concepts such as ecosystem services and resilience, nature is framed as both a solution and an aesthetic asset. However, this framing often leads to exclusionary practices, where access to high-quality green space is unevenly distributed. Semi-private green areas dominate, while public spaces are highly designed and functionally narrow. The planning emphasizes future benefits, creating a temporal displacement that defers access and accountability. Participatory structures are present but seem largely symbolic, favoring technical expertise over meaningful public influence. The study concludes that sustainability in Västra Hamnen is shaped by spatial and institutional inequities. Green infrastructure serves as both material landscape and discursive tool—produced through power and capital. Achieving equitable urban nature requires shifting from a technocratic to a pluralistic planning paradigm that acknowledges diverse needs, uses, and rights to the city.
Keywords: Blue green infrastructure (BGI); Urban Political Ecology; Spatial justice; Planning discourse; Urban Green Equity